Slow virus diseases of the sheep and goat in Greece: I. Progressive pneymonia (Maedi) and pulmonary adenomatosis (Jaagsiekte) - ΣΕΪΜΕΝΗΣ, Α.; ΣΚΟΥΛΑΣ, Ε.; ΠΑΠΑΔΟΠΟΥΛΟΣ, XP.; ΜΑΣΤΡΟΠΑΝΝΗ, Μ.; ΜΑΓΓΑΝΑ, Ο.; ΣΤΟΦΟΡΟΣ, Ε.; ΣΚΥΡΙΑΝΟΣ, Γ.; ΜΕΝΑΣΕ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
Among the slow virus diseases of the sheep, Pulmonary Adenomatosis (Jaagsiekte) and Progressive Pneumonia (Maedi), were reported in Greece in 1952 for the first and in 1968 for the second. Cases of both the above diseases have been recognised in flocks of sheep in various parts of the country ever since. All data collected show a far wider extension of Maedi than Jaagsiekte does. Clinical features, gross and microscopic lesions of both the diseases are discribed. Proposals for a survey on national level are made, especially for Maedi, to be followed by adequate measures in order to control these diseases.